Sacral Nerve Stimulation Fails to Offer Long-term Benefit in Patients With Slow-Transit Constipation. Issue 9 (September 2016) - Patton, Vicki; Stewart, Peter; Lubowski, David Z.; Cook, Ian J.; Dinning, Phil G.
Abstract : BACKGROUND: Sacral nerve stimulation is proposed as a treatment for slow-transit constipation. However, in our randomized controlled trial we found no therapeutic benefit over sham stimulation. These patients have now been followed-up over a long-term period. OBJECTIVE: The purpose of this study was to assess the long-term efficacy of sacral nerve stimulation in patients with scintigraphically confirmed slow-transit constipation. DESIGN: This study was designed for long-term follow-up of patients after completion of a randomized controlled trial. SETTINGS: It was conducted at an academic tertiary public hospital in Sydney. PATIENTS: Adults with slow-transit constipation were included. MAIN OUTCOME MEASURES: At the 1- and 2-year postrandomized controlled trial, the primary treatment outcome measure was the proportion of patients who reported a feeling of complete evacuation on >2 days per week for ≥2 of 3 weeks during stool diary assessment. Secondary outcome was demonstration of improved colonic transit at 1 year. RESULTS: Fifty-three patients entered long-term follow-up, and 1 patient died. Patient dissatisfaction or serious adverse events resulted in 44 patients withdrawing from the study because of treatment failure by the end of the second year. At 1 and 2 years, 10 (OR = 18.8% (95% CI, 8.3% to 29.3%)) and 3 patients (OR = 5.7% (95% CI, –0.5% to 11.9%)) met the primary outcome measure. Colonic isotope retention at 72 hours did not differ between baseline (OR = 75.6% (95% CI, 65.7%–85.6%)) and 1-year follow-up (OR = 61.7% (95% CI, 47.8%–75.6%)). LIMITATIONS: This study only assessed patients with slow-transit constipation. CONCLUSIONS: In these patients with slow-transit constipation, sacral nerve stimulation was not an effective treatment.